Pengembangan Aparatur berbasis Kompetensi di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu di Kabupaten Demak Provinsi Jawa Tengah - Dwi Ayu Sulistyaningrum; Ika Sartika; Gasper Liauw (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2021)
This research is motivated by the duties and functions of an ASN to provide services to the community. The development of industrial revolution 4.0 currently impacts the government bureaucracy required to be professional, have integrity, and serve the community. Departing from the above thought, the authors are interested in researching with the title "Competency-Based Apparatus Development in the Investment Service and One Stop Services, Demak Regency, Central Java Province." The purpose of this research is to find out how the development of competency-based apparatus in the Department of Investment and One Stop Services of Demak Regency. The writing of this final report uses a type of qualitative research with descriptive methods and an inductive approach. The theoretical aspect based on technical competence, conceptual competence, and competence for life has not been implemented optimally due to several obstacles, including limited budget and infrastructure, age and motivation factors, and incompatibility of training with competence. Some of the efforts made to deal with these problems include proposing additional budgets and completeness of infrastructure and providing leadership roles to increase motivation. The author's suggestions are the need to strengthen communication, consultation and coordination, and innovation activities such as in-house training and knowledge transfer.